Determination of Phage Antibody Affinities to Antigen by a Microbalance Sensor System. (May 1999) - Hengerer, A.; Kösslinger, C.; Decker, J.; Hauck, S.; Queitsch, I.; Wolf, H.; Dübel, S.
Over the past decade, phage display has maturated to be a frequently used method for the generation of monoclonal antibodies of human origin. The essential step of this method is the "biopanning" of phage carrying functional antibody fragments on their surface on an immobilized antigen. The screening of large combinatorial gene libraries with this method usually leads to a set of diverse clones specifically binding to the antigen that need to be characterized further. Beside its specificity, the key parameter to be determined is the affinity of the recombinant antibody fragment to its antigen. Here, we present a mass sensitive microsensor method that allows the estimation of antibody affinity directly from the phage supernatant. Binding of phage antibodies to the antigen immobilized on a quartz crystal microbalance (QCM) induced a mass dependent decrease in frequency. This principle was used to determine the apparent affinity of a single-chain (sc)Fv antibody against the RNA polymerase of Drosophila melanogaster presented on the surface of a filamentous phage (M13) from its association and dissociation rates. The apparent affinity obtained is in accordance with the affinity of the scFv fragment as determined by conventional equilibrium enzyme-linked immunosorbent assay (ELISA) and plasmon resonance methods.